Forecasting Palm Oil Price Movements In Malaysia: Empirical Evidence from the Malaysian Palm Oil Futures Market. - Amran, Zulfathi (2010)
The palm oil industry is one of the main commodity industries in South East Asia. This is the case for the two main producers and exporters of crude palm oil in the world, Malaysia and Indonesia, and thus there is an importance placed on the trading of the commodity in Malaysia, especially for hedging purposes for the producers. This is because; the main use of the product is for exporting purposes rather than for consumption, and thus it is important if there is a tool that the producers or traders can use to forecast the crude palm oil price movements and take actions accordingly to minimize their risk exposure. Yet, majority of the traders in Malaysia do not use the crude palm oil futures when hedging, and used the other commodities such as soy bean, which will then expose them to the problems associated with cross hedging. This paper attempts to find evidence on whether the information embedded in the crude palm oil futures market is able to predict the movements of the spot price. First, the relationship between the spot and futures in the long run is shown to exist with and equilibrium, and these prices are then used in the VECM model as a forecasting tool. When the proposed VECM is compared with the RWM, it was found that the VECM is able to outperform the RWM, both at point forecasting and the timing ability. However, the VECM was not able to outperform the VARD model. This implies that the information embedded in the long run relationship, which is included in the VECM and not VARD, is not particularly important as to forecasting the price movements.